Do lactate levels in the emergency department predict outcome in adult trauma patients? A systematic review. Issue 3 (September 2016) - Baxter, Janie; Cranfield, Kristina Rebecca; Clark, Gabrielle; Harris, Tim; Bloom, Ben; Gray, Alasdair James
Abstract : BACKGROUND: Serum lactate may be associated with clinical outcomes in trauma, even in the absence of physiological abnormality. Sensitive markers of injury and outcomes are needed to guide triage and management of trauma patients within the Emergency Department. We completed a systematic review to determine if lactate levels in adult trauma patients presenting to the Emergency Department were associated with clinical outcomes including mortality. METHODS: A systematic literature search was conducted in August 2014, updated in March 2016, using MEDLINE, Embase, and CINAHL. Abstracts and full texts were screened for inclusion by two independent reviewers using predetermined inclusion and exclusion criteria. Data extraction and quality assessment was performed by each reviewer using a standardized form. A total of 998 studies were screened; 28 studies were included and reviewed. RESULTS: The 28 studies recruited 44, 154 adults in eight countries between 1997 and 2016. Twenty-one studies found a significant association between elevated Emergency Department lactate and risk of mortality. Three studies looked at lactate clearance; two showed poor clearance was an additional determinant of mortality, but the other found no association. Ten studies also found an association between elevated lactate and other clinical outcomes. These included injury severity, Intensive Care Unit admission, length of hospital stay, organ failure, respiratory complications, blood loss, blood product requirement, catecholamine support, or emergency operation. Two studies concluded that lactate levels do not affect management. CONCLUSIONS: This review shows that elevated Emergency Department lactate levels are associated with mortality and may be associated with other clinical outcomes in adult trauma patients. We conclude that lactate is a useful marker of outcome in trauma, in addition to current markers of severity. The potential roles of serial lactate measurement and lactate clearance require further research. LEVEL OF EVIDENCE: Systematic review, level III.